Cervical Vestibular Evoked Myogenic Potentials That Are Absent at 500 Hz But Present at 1000 Hz Are Characteristic of Endolymphatic Hydrops-Related Disease. Issue 5 (September 2021) - Fujimoto, Chisato; Kinoshita, Makoto; Ichijo, Kentaro; Oka, Mineko; Kamogashira, Teru; Sugasawa, Keiko; Kawahara, Takuya; Yamasoba, Tatsuya; Iwasaki, Shinichi
Abstract : Objectives: It remains unclear whether the dominance of 1000 Hz responses over responses at 500 Hz in cervical vestibular evoked myogenic potentials (cVEMPs) are characteristic of endolymphatic hydrops (EH), due to the presence of patients with absent responses at both frequencies. The purpose of the present study is to examine whether the dominant cVEMP responses at 1000 Hz over 500 Hz are characteristic findings of EH-related diseases among patients who show various cVEMP findings. Design: We retrospectively reviewed the medical records of 470 consecutive patients who underwent cVEMP testing with short-tone bursts at both 500 Hz and 1000 Hz. We categorized the cVEMP responses of these 470 patients into the following five groups: (group 1) present responses at both frequencies bilaterally, (group 2) present responses at 500 Hz but absent at 1000 Hz on at least one side, (group 3) absent responses at 500 Hz but present at 1000 Hz on at least one side, (group 4) absent responses at both frequencies on one side and present at both frequencies on the other side, and (group 5) absent responses at both frequencies bilaterally. We compared the proportion of EH-related diseases between each group and the other four groups and then investigated any increased or decreased disease incidence in each group. Results: In group 3, the proportion of EH-related disease was significantly higher ( p < 0.01), and the incidence of an EH-related disease was greatly increased (standard residual value > 3). Conclusions: cVEMPs that are absent at 500 Hz and present at 1000 Hz may be characteristic of EH-related disease. Abstract : Supplemental Digital Content is available in the text.